Identification, Synthesis and Characterization of Impurities of (S)-Mitiglinide Calcium Dihydrate - Umasankara Sastry, T.; Nageswara Rao, K.; Appi Reddy, T.; G, P. (Asian Journal of Chemistry, 2014)
(S)-Mitiglinide Calcium dihydrate (1), an important potent hypoglycemic agent. During laboratory optimization and later in bulk synthesis the formation of various impurities was observed. The method of preparation of most of these impurities is not available in literature. We describe herein the formation, synthesis, preparation and characterization of these impurities.